A correlation study between cervical cancer and sex hormones - Wu, Xian; You, Yitao; Guan, Zhichong; Ban, Yongpiao; Wang, Yiping; Du, Dianhua; Wang, Bo; Wu, Wen; Wen, Yue; Ren, Yixian; Wu, Chunwei; Zhang, Xuelin; et al. (Frontiers in Oncology, 2024)
ObjectiveThe aims of this study were to investigate the association between positive TCT and sex hormone levels and to evaluate the feasibility of change in sex hormone level as a potential predictor of cervical cancer.MethodsWe recruited 910 female participants from the health examination center of a hospital in Guizhou between 2019 and 2023. All participants had undergone both hematologic examinations and cervical cancer screening.ResultsA total of 265 participants had positive TCT screening. Luteinizing hormone, estradiol, prolactin, and progesterone were negatively correlated with positive TCT screening. Age, systolic blood pressure, alanine aminotransferase, aspartate aminotransferase, urea, fasting blood glucose, low-density lipoprotein, total cholesterol, triglyceride, erythrocyte, follicle-stimulating hormone, and testosterone were positively correlated with positive TCT screening. Logistic regression analysis showed that prolactin, red blood cell count, and age were risk factors for cervical cancer, while FSH was a protective factor for cervical cancer. The AUC of FSH and age in the prediction model was 0.701 and 0.705, respectively.ConclusionThe incidence of cervical cancer increases with increased age and follicle poietin level. At the same time, the increase in FSH level has a certain predictive value for the incidence of cervical cancer.